Injectable self-mineralizing composite hydrogels, methods of making and using the same

CN117942432BActive Publication Date: 2026-10-27SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211348065.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-31
Publication Date
2026-10-27
Estimated Expiration
2042-10-31

AI Technical Summary

Technical Problem

然而,由于缺乏矿化成分和成骨因子,传统水凝胶的骨传导性有限

Benefits of technology

[0017]1)本发明提供的可注射性自矿化复合水凝胶能够具有良好的骨传导性,为细胞的存活创造良好的微环境,促进细胞的成骨分化;同时还能提高负载物质的稳定性以及可控释放,能够起到良好的治疗和修复骨缺损的作用;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117942432B_ABST
    Figure CN117942432B_ABST
Patent Text Reader

Abstract

The application discloses an injectable self-mineralization composite hydrogel, a preparation method and application thereof. The preparation method comprises the following steps: modifying norbornene on collagen to obtain norbornene-modified collagen; modifying tetrazine on hyaluronic acid to obtain tetrazine-modified hyaluronic acid; uniformly mixing and reacting the norbornene-modified collagen, the tetrazine-modified hyaluronic acid and a substance with mineralization / bone conduction performance to obtain the injectable self-mineralization composite hydrogel, wherein the substance with mineralization / bone conduction performance comprises calcium sulfate nanorod particles. The preparation method is simple, the obtained hydrogel has controllable solidification time, good biocompatibility, can provide a living environment for cell survival and successfully realize osteogenic differentiation; meanwhile, the stability of calcium sulfate loading can be improved, hydrogel mineralization can be realized, and the hydrogel can play a role in treating and repairing bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a hydrogel material, specifically to an injectable self-mineralizing composite hydrogel for bone repair, its preparation method and application, belonging to the field of tissue engineering material preparation technology. Background Technology

[0002] Bone injuries caused by surgery, trauma, and tumors have always been a major challenge for clinical orthopedic surgeons. Bone tissue is primarily composed of mineralized collagen fibers, forming connective tissue. The excellent self-mineralization / osteogenic properties of bone regeneration materials are crucial for bone tissue regeneration. Current clinical treatments using materials for bone defects, such as alloys, can improve bone defects to some extent, but their non-degradability and non-injectability limit their clinical applicability. Therefore, in the field of tissue engineering materials, bone defect repair treatment remains unresolved, and there is still a significant demand for bone repair materials and their preparation methods. Finding an injectable material with excellent degradability is of great importance for promoting bone repair.

[0003] Extensive research has been conducted on bone repair materials. Among them, three-dimensional hydrogels, with their high water content, ability to mimic natural biological tissues, and provision of a favorable three-dimensional environment for cell growth, have become one of the most promising materials in bone tissue engineering. Controlling the shape of blended hydrogels can improve the precision and accuracy of bone tissue repair. However, due to the lack of mineralizing components and osteogenic factors, traditional hydrogels have limited osteoconductivity. This low osteoconductivity significantly hinders the clinical application of traditional hydrogels. Currently, increasing the osteoconductivity of hydrogels by filling them with various functional nanomaterials to create multifunctional hydrogels is one of the most attractive methods for improving the treatment of bone defects. Clearly, the problem of low osteoconductivity can be addressed by loading hydrogels with osteoconductive substances.

[0004] Given the above background, how to provide an injectable self-mineralizing composite hydrogel that can be well applied to bone defect repair and treatment, not only to provide a good microenvironment for cell survival, improve the osteoconductivity of the material, and promote osteogenic differentiation of cells, but also to achieve the stability and controllable release of the loaded nanomaterials, so as to be well used for bone repair and treatment and realize bone tissue regeneration, has become an urgent technical problem to be solved at this stage. Summary of the Invention

[0005] The main objective of this invention is to provide an injectable self-mineralizing composite hydrogel for bone repair and its preparation method, so as to overcome the shortcomings of the prior art.

[0006] Another object of the present invention is to provide the application of the injectable self-mineralizing composite hydrogel.

[0007] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0008] This invention provides a method for preparing an injectable self-mineralizing composite hydrogel, comprising:

[0009] Using an injectable hydrogel as a matrix, a substance with mineralization / osteogenic properties is incorporated into the injectable hydrogel, and an injectable self-mineralizing composite hydrogel is prepared by bioorthogonal reaction.

[0010] In some embodiments, the preparation method specifically includes:

[0011] Norbornene was modified onto collagen to obtain norbornene-modified collagen;

[0012] Tetraazine was modified onto hyaluronic acid to obtain tetraazine-modified hyaluronic acid;

[0013] The norbornene-modified collagen, tetraazine-modified hyaluronic acid, and a substance with mineralization / bone conduction properties are mixed and reacted uniformly to obtain an injectable self-mineralizing composite hydrogel.

[0014] The present invention also provides an injectable self-mineralizing composite hydrogel prepared by the aforementioned preparation method, which includes a substance with mineralizing / osteoconductive properties dispersed within the hydrogel.

[0015] This invention also provides the application of the aforementioned injectable self-mineralizing composite hydrogel in the preparation of products with bone defect repair function.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] 1) The injectable self-mineralizing composite hydrogel provided by the present invention has good osteoconductivity, creates a good microenvironment for cell survival, and promotes osteogenic differentiation of cells; at the same time, it can also improve the stability and controllable release of the loaded material, and play a good role in treating and repairing bone defects.

[0018] 2) This invention provides a method for preparing a composite hydrogel based on bioorthogonal reactions, which can be used to prepare an injectable bone repair therapeutic agent. This agent is injectable in situ and promotes bone healing in vivo. Furthermore, the preparation method is simple and allows for large-scale production.

[0019] 3) The injectable self-mineralizing composite hydrogel obtained by the present invention has good biocompatibility, can provide a three-dimensional survival environment for cells, improve cell adhesion and proliferation on the hydrogel, and can be applied to osteogenic differentiation research. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram illustrating the preparation mechanism of the injectable self-mineralizing composite hydrogel obtained in a typical embodiment of the present invention.

[0022] Figure 2a and Figure 2b This is an appearance diagram of calcium sulfate nanorod particles obtained in a typical embodiment of the present invention.

[0023] Figures 3a-3f This is an appearance diagram of the injectable self-mineralizing composite hydrogel obtained in a typical embodiment of the present invention.

[0024] Figure 4a , Figure 4b , Figure 4c This is an in vitro mineralization appearance diagram of the injectable self-mineralizing composite hydrogel obtained in a typical embodiment of the present invention.

[0025] Figure 5a and Figure 5b This is a proliferation diagram of osteoblasts obtained from an injectable self-mineralizing composite hydrogel in a typical embodiment of the present invention.

[0026] Figure 6 This is a schematic diagram of ALP and ARS staining, markers of osteogenic differentiation, obtained from an injectable self-mineralizing composite hydrogel in a typical embodiment of the present invention.

[0027] Figure 7a , Figure 7b , Figure 7c This is a schematic diagram illustrating the expression of osteogenic differentiation-specific genes OPN, RunX2, and OCN in an injectable self-mineralizing composite hydrogel obtained in a typical embodiment of the present invention.

[0028] Figure 8a , Figure 8b , Figure 8c These are, respectively, micro-CT 3D reconstruction images of in vivo tibial defect repair using the injectable self-mineralizing composite hydrogel obtained in a typical embodiment of the present invention, bone volume fraction maps (BV / TV) of different defect areas, and bone mineral density maps (BMD) of different defect locations. Detailed Implementation

[0029] Addressing the existing needs for bone defect repair and the shortcomings of current bone injury repair scaffolds and materials, the main objective of this invention is to solve the aforementioned problems by providing an injectable composite hydrogel that can effectively repair bone defects. Furthermore, the preparation method of this invention is simple, and the resulting hydrogel possesses highly efficient mineralization and osteoconductive properties, creating a favorable microenvironment for cell survival and promoting osteogenic differentiation. Simultaneously, it enhances the stability and controllable release of the loaded material, thus achieving excellent therapeutic and repair effects on bone defects.

[0030] The following will further explain the technical solution, its implementation process, and its principles. However, it should be understood that within the scope of this invention, the above-mentioned technical features of this invention and the technical features specifically described below (in embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here.

[0031] As one aspect of the technical solution of the present invention, it relates to a method for preparing an injectable self-mineralizing composite hydrogel for treating bone defects, comprising: using an injectable hydrogel as a matrix, which includes a polymer and water; doping a substance with mineralization / bone conduction properties into the injectable hydrogel; and preparing the injectable self-mineralizing composite hydrogel by a bioorthogonal reaction, wherein the polymer is collagen and hyaluronic acid, etc.

[0032] As one of the preferred embodiments, the preparation method includes: using collagen (Col) and hyaluronic acid (HA) as a matrix, incorporating a substance with mineralization / osteoconductivity properties into a hydrogel precursor solution, and preparing an injectable self-mineralizing composite hydrogel based on a bioorthogonal reaction.

[0033] As one of the preferred embodiments, the preparation method of the injectable self-mineralizing composite hydrogel specifically includes:

[0034] Norbornene was modified onto collagen to obtain norbornene-modified collagen;

[0035] Tetraazine was modified onto hyaluronic acid to obtain tetraazine-modified hyaluronic acid;

[0036] The norbornene-modified collagen, tetraazine-modified hyaluronic acid, and a substance with mineralization / bone conduction properties are mixed and reacted uniformly to obtain an injectable self-mineralizing composite hydrogel.

[0037] As one preferred embodiment, the mineralizing / osteogenic material is calcium sulfate nanorod particles, but not limited to this. Calcium sulfate is a commonly used bone cement filler in clinical practice. Compared with other bone cement materials (such as polymethyl methacrylate), calcium sulfate has better osteoconductivity (self-mineralization) and biodegradability. However, its rapid degradation rate results in poor stability in vivo. By uniformly loading calcium sulfate into a hydrogel, its stability can be effectively improved; simultaneously, calcium sulfate can enhance the osteoconductivity of the hydrogel, increase cell proliferation and differentiation capacity, and promote bone tissue regeneration and repair.

[0038] Furthermore, the calcium sulfate nanorod particles have a length range of 100–200 nm and are uniformly dispersed within the hydrogel.

[0039] As one of the preferred embodiments, the method for preparing the calcium sulfate nanorod particles includes: reacting a mixed system containing calcium salt, sulfuric acid and a first solvent at 20-30°C for 6-24 hours to obtain calcium sulfate nanorod particles.

[0040] Specifically, the preparation method of the calcium sulfate nanorod particles includes: using a certain concentration of sulfuric acid and calcium nitrate solution to prepare calcium sulfate nanorod particles with controllable particle size, uniform size and high dispersion through a simple chemical method; after the reaction is completed, the particles are repeatedly centrifuged and washed, and the precipitate obtained is calcium sulfate nanorod particles.

[0041] As one more specific embodiment, the method for preparing the calcium sulfate nanorod particles specifically includes:

[0042] Sulfuric acid and the first solvent are mixed evenly to form a first mixed system;

[0043] The calcium salt and the first solvent are mixed evenly to form a second mixed system;

[0044] The first mixture was added dropwise to the second mixture at a rate of 0.4–1.0 mL / min, and the mixture was mixed evenly to form a third mixture. The solid obtained from the reaction was freeze-dried to obtain calcium sulfate nanorod particles.

[0045] In some more specific embodiments, the first mixed system formed by uniformly mixing sulfuric acid and the first solvent needs to be slowly dripped into the second mixed system formed by mixing calcium salt and the first solvent to form a third mixed system.

[0046] Furthermore, the preparation method further includes: after the reaction of the third mixing system is completed, centrifugation and washing are performed to obtain a precipitate, which is then freeze-dried to obtain calcium sulfate nanorod particles.

[0047] Furthermore, the calcium salt may include any one or a combination of two or more of calcium nitrate, calcium carbonate, calcium phosphate, etc., but is not limited thereto.

[0048] Furthermore, the first solvent may include anhydrous ethanol and / or methanol, but is not limited thereto.

[0049] Furthermore, the volume ratio of the first solvent in the first mixed system to the first solvent in the second mixed system is 5 to 10:1.

[0050] Furthermore, the molar ratio of calcium ions in the calcium salt to sulfate ions in the sulfuric acid is 1 to 2:1.

[0051] As one of the preferred embodiments, the method for preparing the norbornene-modified collagen includes:

[0052] A fourth mixture containing collagen, a condensing agent, and a second solvent is reacted at 0–10°C for 10–30 min. Then, norbornene is added and mixed evenly to form a fifth mixture. The fifth mixture is then reacted at 15–30°C for 12–24 h to obtain norbornene-modified collagen.

[0053] Furthermore, the method for preparing norbornene-modified collagen further includes: after the reaction of the fifth mixing system is completed, dialyzing the obtained reaction mixture for 1 to 3 days, and then freeze-drying it to obtain norbornene-modified collagen.

[0054] As one preferred embodiment, the method for preparing the tetrazine-modified hyaluronic acid includes:

[0055] The sixth mixture containing the third solvent, tetrazine, and condensing agent is reacted under nitrogen for 10–30 min. Then, hyaluronic acid salt is added and mixed evenly to form the seventh mixture. The seventh mixture is then reacted at 15–30 °C for 10–20 h to obtain tetrazine-modified hyaluronic acid.

[0056] Furthermore, the method for preparing the tetrazine-modified hyaluronic acid further includes: after the reaction of the seventh mixing system is completed, dialyzing the obtained reaction mixture for 1 to 3 days, and then freeze-drying it to obtain the tetrazine-modified hyaluronic acid.

[0057] As one of the preferred options, the condensing agent includes any one or a combination of two of the following: benzotriazole-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate (Carter condensing agent) and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, but is not limited thereto.

[0058] Furthermore, the second or third solvent includes any one or a combination of two or more of 2-(N-morpholino)ethanesulfonic acid, dichloromethane, tetrahydrofuran, dimethyl sulfoxide, etc., but is not limited thereto.

[0059] As one of the preferred embodiments, the preparation method may include: uniformly mixing calcium sulfate nanorod particles in a solution of norbornene-modified collagen or tetraazine-modified hyaluronic acid.

[0060] As one of the preferred embodiments, the volume ratio of the calcium sulfate nanorod particles, norbornene-modified collagen, and tetraazine-modified hyaluronic acid is 0-5:100:100.

[0061] Another aspect of the present invention provides an injectable self-mineralizing composite hydrogel prepared by the aforementioned preparation method, comprising a substance having mineralizing / osteoconductive properties dispersed within the hydrogel.

[0062] The hydrogel is an in-situ injectable hydrogel based on the bioorthogonal reaction between tetrazine and norbornene.

[0063] As one preferred embodiment, the composite hydrogel contains components such as calcium sulfate nanorod particles, simultaneously achieving the preparation of the hydrogel and highly dispersed calcium sulfate nanorod particles. Therefore, this invention optimizes the calcium sulfate / hydrogel system by preparing a hydrogel containing highly dispersed calcium sulfate nanorod particles. This hydrogel system not only promotes cell proliferation and differentiation but also enables the controlled release of nanoparticles, thereby promoting bone defect repair.

[0064] As one of the preferred embodiments, the content of the component with mineralization / osteoconductive properties in the injectable self-mineralizing composite hydrogel is less than 5 wt%.

[0065] Furthermore, the injectable self-mineralizing composite hydrogel has a porous structure with pores having a diameter of 200–400 μm.

[0066] Another aspect of the present invention provides the application of the aforementioned injectable self-mineralizing composite hydrogel in the preparation of products with bone defect repair function.

[0067] Furthermore, the injectable self-mineralizing composite hydrogel can be used for cell culture to promote cell proliferation and osteogenic differentiation.

[0068] Furthermore, the application of the injectable self-mineralizing composite hydrogel includes: applying the composite hydrogel to clinical problems related to bone defects.

[0069] Furthermore, the application of the injectable self-mineralizing composite hydrogel includes: using the composite hydrogel for in-situ bone healing of complex shapes.

[0070] Furthermore, the application of the injectable self-mineralizing composite hydrogel includes its use in the preparation of drugs for treating bone defects after loading the composite hydrogel with relevant mineralizing functional particles.

[0071] Another aspect of the present invention provides the use of the aforementioned injectable self-mineralizing composite hydrogel in an in vitro environment for self-mineralization.

[0072] Another aspect of the present invention provides the use of the aforementioned injectable self-mineralizing composite hydrogel in the field of osteoblast culture.

[0073] Another aspect of the present invention provides the use of the aforementioned injectable self-mineralizing composite hydrogel in the field of bone tissue engineering.

[0074] The preparation method provided by the present invention is simple, the curing time of the obtained hydrogel is controllable, the biocompatibility is good, it can provide a living environment for cell survival and successfully achieve osteogenic differentiation; at the same time, it can also improve the stability of calcium sulfate loading, realize hydrogel mineralization, and play a role in treating and repairing bone defects.

[0075] To make the objectives, technical solutions, and applications of this invention clearer, the technical solutions of this invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs; implementation conditions not specified are generally conditions in conventional experiments.

[0076] Example 1

[0077] An injectable self-mineralizing composite hydrogel for bone repair, such as Figure 1 As shown, calcium sulfate nanorods can be uniformly immobilized in a hydrogel to form an injectable, self-mineralizing composite hydrogel. Specifically, it is prepared using the following method:

[0078] Step 1: Add concentrated sulfuric acid to ethanol to form a first mixed system with a concentration of 2mM;

[0079] Step 2: Add calcium nitrate to anhydrous ethanol to form a second mixed system with a concentration of 0.2M;

[0080] Step 3: The first mixture is gradually and slowly added to the second mixture at a rate of 0.4 mL / min using a peristaltic pump to form the third mixture, and the mixture is reacted at room temperature (25°C) for 6 hours.

[0081] Step 4: After the reaction is complete, the product is centrifuged, washed, and freeze-dried to obtain calcium sulfate nanorod particles.

[0082] Step 5: The fourth mixture containing collagen, benzotriazole-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, and tetrahydrofuran is reacted at 4°C for 30 min. Then, norbornene is added and mixed evenly to form the fifth mixture. The fifth mixture is then reacted at 15°C for 24 h to obtain norbornene-modified collagen.

[0083] Step Six: The sixth mixed system, containing dimethyl sulfoxide, tetrazine, benzotriazine-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, etc., is reacted under nitrogen for 30 min. Then, hyaluronic acid salt is added and mixed evenly to form the seventh mixed system. The seventh mixed system is then reacted at room temperature (25°C) for 20 h to obtain tetrazine-modified hyaluronic acid.

[0084] Step 7: After the reaction of the mixture is completed, the obtained reaction mixture is dialyzed for 3 days and then freeze-dried to obtain norbornene-modified collagen and tetraazine-modified hyaluronic acid.

[0085] Step 8: Dissolve norbornene-modified collagen and tetraazine-modified hyaluronic acid separately in phosphate-buffered saline (PBS) solution, then mix thoroughly to form a Col-HA hydrogel. Preferably, the molar ratio of collagen to hyaluronic acid is 1:1.

[0086] Step Nine: The injectable Col-HA hydrogel has a porous structure, wherein the pore size is 200–400 μm, such as… Figure 3a and Figure 3b As shown.

[0087] Step 10: Place the injectable Col-HA hydrogel in simulated body fluid and soak it at 37°C for 7 days before removing it. Figure 4a This is an image showing the appearance of Col-HA in vitro mineralization.

[0088] Example 2

[0089] An injectable self-mineralizing composite hydrogel for bone repair was prepared by the following method:

[0090] Step 1: Add concentrated sulfuric acid to ethanol to form a first mixed system with a concentration of 2mM;

[0091] Step 2: Add calcium nitrate to anhydrous ethanol to form a second mixed system with a concentration of 0.2M;

[0092] Step 3: The first mixture is gradually and slowly added to the second mixture at a rate of 0.6 mL / min using a peristaltic pump to form the third mixture, and the mixture is reacted at 20°C for 24 h.

[0093] Step 4: After the reaction is complete, the particles are centrifuged, washed, and freeze-dried to obtain calcium sulfate nanorod particles, and their morphology is characterized as follows: Figure 2a and Figure 2b As shown.

[0094] Step 5: The fourth mixture containing collagen, benzotriazole-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, and tetrahydrofuran is reacted at 0°C for 30 min. Then, norbornene is added and mixed evenly to form the fifth mixture. The fifth mixture is then reacted at 25°C for 20 h to obtain norbornene-modified collagen.

[0095] Step Six: The sixth mixed system, containing dimethyl sulfoxide, tetrazine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, etc., is reacted under nitrogen for 20 min. Then, hyaluronic acid salt is added and mixed evenly to form the seventh mixed system. The seventh mixed system is then reacted at 15°C for 20 h to obtain tetrazine-modified hyaluronic acid.

[0096] Step 7: After the reaction of the mixture is completed, the obtained reaction mixture is dialyzed for 2 days and then freeze-dried to obtain norbornene-modified collagen and tetraazine-modified hyaluronic acid.

[0097] Step 8: Dissolve norbornene-modified collagen and tetrazine-modified hyaluronic acid separately in a 1 w / v solution of calcium sulfate nanoparticles, then mix thoroughly to form a composite hydrogel (1% CSN@Col-HA). The volume ratio of the calcium sulfate nanoparticles, norbornene-modified collagen, and tetrazine-modified hyaluronic acid is 1:100:100.

[0098] Step Nine: The injectable composite hydrogel has a porous structure, wherein the pore size is 200–400 μm, such as… Figure 3c and Figure 3d As shown.

[0099] Step 10: Place the injectable 1% CSN@Col-HA hydrogel in simulated body fluid and remove it after soaking at 37°C for 7 days. Figure 4b Appearance of 1% CSN@Col-HA in vitro mineralization.

[0100] Example 3

[0101] An injectable self-mineralizing composite hydrogel for bone repair was prepared by the following method:

[0102] Step 1: Add concentrated sulfuric acid to methanol to form a first mixed system with a concentration of 2mM;

[0103] Step 2: Add calcium nitrate to anhydrous ethanol to form a second mixed system with a concentration of 0.2M;

[0104] Step 3: The first mixture is gradually and slowly added to the second mixture at a rate of 1.0 mL / min using a peristaltic pump to form the third mixture, and the mixture is reacted at 30°C for 6 hours.

[0105] Step 4: After the reaction is complete, the product is centrifuged, washed, and freeze-dried to obtain calcium sulfate nanorod particles.

[0106] Step 5: The fourth mixture containing collagen, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and dimethyl sulfoxide is reacted at 10°C for 10 min. Then, norbornene is added and mixed evenly to form the fifth mixture. The fifth mixture is then reacted at 30°C for 12 h to obtain norbornene-modified collagen.

[0107] Step Six: The sixth mixed system, containing dimethyl sulfoxide, tetrazine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, etc., is reacted under nitrogen for 10 min. Then, hyaluronic acid salt is added and mixed evenly to form the seventh mixed system. The seventh mixed system is then reacted at 30°C for 10 h to obtain tetrazine-modified hyaluronic acid.

[0108] Step 7: After the reaction of the mixture is completed, the obtained reaction mixture is dialyzed for 1 day and then freeze-dried to obtain norbornene-modified collagen and tetraazine-modified hyaluronic acid.

[0109] Step 8: Dissolve norbornene-modified collagen and tetrazine-modified hyaluronic acid separately in a 5 w / v solution of calcium sulfate nanoparticles, then mix thoroughly to form a composite hydrogel (5% CSN@Col-HA). The volume ratio of the calcium sulfate nanoparticles, norbornene-modified collagen, and tetrazine-modified hyaluronic acid is 5:100:100.

[0110] Step Nine: The injectable composite hydrogel has a porous structure, wherein the pore size is 200–300 μm, such as… Figure 3e and Figure 3f As shown.

[0111] Step 10: Place the injectable 5% CSN@Col-HA hydrogel in simulated body fluid and remove it after soaking at 37°C for 7 days. Figure 4cThe image shows the appearance of 5% CSN@Col-HA in vitro mineralization, indicating that 5% CSN@Col-HA has in vitro mineralization capabilities.

[0112] Example 4

[0113] The results of cell compatibility testing for the injectable composite hydrogels obtained in Examples 1-3 are as follows: Figure 5a and Figure 5b As shown.

[0114] The survival and proliferation of cells on the surface of the injectable composite hydrogels in Examples 1-3 were determined using calcein staining and the MTT assay (cell viability analysis).

[0115] In some embodiments, the cells are osteoblastic progenitor cells (MC3T3-E1).

[0116] Specific operating method: Digest and centrifuge the osteogenic progenitor cells cultured in complete culture medium and count them; seed the cells on the surface of the sterile injectable composite hydrogel (Φ10mm×1mm) obtained in Examples 1 to 3, add complete culture medium, and incubate in a 5% CO2, 37℃ incubator.

[0117] After 7 days of culture, the culture medium was aspirated, and the cells were washed three times with PBS. Cell viability was then assessed using a Live / Dead assay kit under laser confocal microscopy at 488 / 561 nm. Live cells fluoresced green with calcein, while dead cells stained red. The control group consisted of cells cultured alone.

[0118] like Figure 5a The figure shows the cell survival on the surface of the injectable composite hydrogel obtained in Examples 1-3, indicating that the examples of the present invention are non-toxic to cells.

[0119] After 1, 4 and 7 days of culture, the culture medium was removed, MTT was added and mixed thoroughly, and the mixture was incubated in a 5% CO2, 37℃ incubator for 4 hours. 100 μL was then taken into a 96-well plate and the OD value was measured at 450 nm using a microplate reader.

[0120] Figure 5b The figure shows the cell proliferation on the surface of the injectable composite hydrogels obtained in Examples 1-3, indicating that the hydrogels obtained by the present invention have low toxicity and good biocompatibility, and the cells proliferate significantly after 7 days of culture.

[0121] Example 5

[0122] The results of detecting osteogenic differentiation of the injectable composite hydrogels obtained in Examples 1-3 are as follows: Figure 6 As shown.

[0123] Alkaline phosphatase (ALP) is an early marker of osteoblast differentiation, and mineralized nodules are a sign of mature osteoblast differentiation. This invention uses an ALP staining kit and an osteoblast mineralized nodule staining (ARS) kit to determine the osteogenic differentiation of cells in the injectable composite hydrogels of Examples 1-3. Specific procedures: Osteogenic precursor cells cultured in complete culture medium were digested, centrifuged, and counted; the cells were seeded onto the surface of sterile injectable composite hydrogels (Φ10mm×1mm) obtained in Examples 1-3, osteogenic differentiation culture medium was added, and the cells were incubated in a 5% CO2, 37°C incubator. A control group consisted of simple cell culture.

[0124] After 14 days of culture, the culture medium was aspirated, and the cells were washed three times with PBS. The staining was then observed under an upright microscope using an ALP and ARS kit. ALP binds to calcium ions, appearing black, while ARS chelates calcium ions in mineralized nodules, appearing red.

[0125] Figure 6 The figures show the osteogenic differentiation of cells on the surface of the injectable composite hydrogels obtained in Examples 1-3. Using MC3T3-E1 cells alone as a control group, the results indicate that the cells obtained from the composite hydrogels in Examples 1-3 possess a high osteogenic differentiation capacity.

[0126] Example 6

[0127] Osteogenic differentiation of osteogenic progenitor cells on the surface of injectable composite hydrogels obtained in Examples 1-3 was detected. The expression of osteogenic differentiation-specific genes osteopontin (OPN), dwarfism-associated transcription factor 2 (RunX2), and osteocalcin (OCN) on the surface of the injectable hydrogels obtained in Examples 1-3 was measured using reverse transcription-polymerase chain reaction (RT-PCR) to characterize the degree of osteogenic differentiation on the surface of the injectable hydrogels obtained in Examples 1-3. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was selected as an internal control gene. Specific procedures: Osteogenic progenitor cells cultured in complete culture medium were digested, centrifuged, and counted; cells were seeded on the surface of sterilized injectable composite hydrogels (Φ10mm×1mm) obtained in Examples 1-3, osteogenic differentiation culture medium was added, and the cells were incubated in a 5% CO2, 37℃ incubator. Fresh culture medium was added every other day, and RNA was extracted after 7, 14, and 21 days of culture.

[0128] Step 1: Total RNA extraction. Add RNAiso Plus lysis buffer to the wells of the composite hydrogel and cell co-culture plate and lyse on ice for 15 min. After lysis, pipette several times to fully lyse any unlysed cells. Aspirate the lysed cell suspension and incubate at room temperature for 10 min. Chloroform was added to the cell suspension, vortexed for 15 seconds, and allowed to stand at room temperature for 5 minutes before centrifugation (12000 rpm, 15 minutes). After centrifugation, the liquid in the tube separated into three layers. The uppermost colorless liquid was transferred to an enzyme-free centrifuge tube, and an equal volume of pre-chilled isopropanol was added. The mixture was gently inverted and incubated overnight at -20°C. Subsequently, the tube was centrifuged at 12000 rpm for 15 minutes at 4°C, the supernatant was discarded, and the white precipitate at the bottom of the tube was retained. 75% ethanol prepared with DEPC water was added to the tube, and the mixture was gently inverted and centrifuged at 12000 rpm for 5 minutes at 4°C. The supernatant was discarded, and the precipitate in the tube was dried in a clean bench. DEPC water was added dropwise to the dried centrifuge tube to completely dissolve the RNA. The concentration of the extracted RNA was measured using a BioPhotometer ultraviolet spectrophotometer. The purity of the extracted RNA was assessed by recording the OD values ​​of the sample RNA at wavelengths of 260 nm and 280 nm and calculating the ratio between the two values. If the ratio is between 1.8 and 2.0, it indicates that the extracted RNA is of high purity; if the ratio is less than 1.8 or greater than 2.0, it indicates that the sample RNA is impure.

[0129] Step 2: Reverse transcription of cDNA. Add 1 μL of sample RNA solution, 1 μL of OligodT Primer, 1 μL of Random 6mers, 1 μL of Primer Script RT Enzyme Mix I, and 4 μL of 5×PrimeScript Buffer to a 200 μL enzyme-free centrifuge tube. Finally, add RNase-free dH2O to bring the total reaction volume to 20 μL. Perform reverse transcription using a reverse transcriptase instrument. After transcription, dilute the obtained cDNA 5-fold and store at -80℃ for later use.

[0130] Step 3: qRT-PCR amplification reaction. Following the qRT-PCR amplification system table, add 2 μL cDNA, 6.8 μL dd H2O, 10 μL SYBR Premix Ex Taq, 0.4 μL upstream primers (PCR Forward Primers), 0.4 μL downstream primers (PCR Reverse Primers), and 0.4 μL RoxReference Dye II to each well of the eight-tube set. Mix well, briefly centrifuge, and then place the eight-tube set on a quantitative PCR instrument using the following program: 95℃ for 10 min, 95℃ for 30 sec, 45 cycles (60℃ for 30 sec, 72℃ for 30 sec), 72℃ for 10 min. This will yield the expression levels of osteogenic differentiation-specific genes osteopontin (OPN), dwarfism-associated transcription factor 2 (RunX2), and osteocalcin (OCN). Figures 7a-7c As shown, cells can differentiate into osteogenic cells normally on the surface of the injectable composite hydrogels obtained in Examples 1-3.

[0131] Example 7

[0132] The in vivo tibial defect repair effect of the injectable composite hydrogels obtained in Examples 1-3 was evaluated using micro-CT, and the results are as follows: Figures 8a-8c As shown.

[0133] Figure 8a 3D reconstructed image of the tibia after composite hydrogel repair via micro-CT; Figure 8b Bone volume fraction (BV / TV) in different defect areas; Figure 8c Bone mineral density (BMD) at different defect locations in different groups. The control group received only saline treatment for tibial defects.

[0134] like Figure 8a As shown, the hydrogels obtained in Examples 1-3 exhibited varying degrees of new bone formation from the edge to the center. However, the tibia in the control group still showed a large area of ​​bone defect. Conversely, in other groups, especially in Example 3, the area of ​​tibial bone defect repair significantly increased. This indicates that calcium sulfate nanoparticles can effectively promote bone defect repair. Compared with Example 3 (69±5%), Example 2 (53±8%), and Example 1 (43±10%), the control group had the lowest BV / TV score, indicating that calcium sulfate nanoparticles have a significant advantage in promoting bone healing and regeneration. The above examples fully demonstrate that Examples 1-3 have excellent in vivo bone defect repair effects. This may be related to the following factors: (1) the osteogenic effect of the hydrogel; (2) the calcium sulfate in the composite hydrogel, which is beneficial for osteogenic differentiation of cells and the repair of self-bone tissue.

[0135] Compare with Example 1

[0136] Generally, gelation is achieved using organic chemical reagents or ultraviolet light polymerization. However, organic reagents are cytotoxic, and ultraviolet light polymerization is not conducive to cell growth, thus limiting their application in biomedicine.

[0137] Compared with Comparative Example 1, the composite hydrogels obtained in Examples 1-3 of the present invention are based on bioorthogonal molding. Bioorthogonal reactions are reactions that are carried out without interfering with the organism itself, resulting in good biocompatibility and benefiting cell growth and proliferation.

[0138] Compare with Example 2

[0139] Generally, curing methods such as ultraviolet light polymerization make it difficult to achieve injectability of hydrogels, which limits their application in some minimally invasive bone defect surgeries.

[0140] Compared with Comparative Example 2, the composite hydrogels obtained in Examples 1-3 of the present invention are injectable and have controllable curing time, and have a wider range of biological applications than conventional hydrogels.

[0141] In summary, through the above-mentioned technical solutions of the present invention, the injectable hydrogel for bone defect repair of the present invention has good biocompatibility, low toxicity, can provide a survival environment for cells, improve cell proliferation on the scaffold, and achieve osteogenic differentiation and bone defect repair.

[0142] It should be understood that the examples described above are merely illustrative of the technical concept and features of the present invention, intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and should not be used to limit the scope of protection of the present invention. All equivalent transformations or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing an injectable self-mineralizing composite hydrogel, characterized in that, include: Using an injectable hydrogel as a matrix, a substance with mineralizing / osteogenic properties is doped into the injectable hydrogel, and an injectable self-mineralizing composite hydrogel is prepared by bioorthogonal reaction, specifically including: The fourth mixture containing collagen, condensing agent and second solvent is reacted at 0-10 °C for 10-30 min, then norbornene is added and mixed evenly to form the fifth mixture. The fifth mixture is then reacted at 15-30 °C for 12-24 h to obtain norbornene-modified collagen. The sixth mixture containing the third solvent, tetrazine and condensing agent is reacted under nitrogen atmosphere for 10-30 min, then hyaluronic acid salt is added and mixed evenly to form the seventh mixture, and the seventh mixture is reacted at 15-30 °C for 10-20 h to obtain tetrazine-modified hyaluronic acid; The norbornene-modified collagen, tetraazine-modified hyaluronic acid, and a substance with mineralization / bone conduction properties are mixed and reacted uniformly to obtain an injectable self-mineralizing composite hydrogel. The mineralization / bone conduction material includes calcium sulfate nanorod particles with a length of 100–200 nm; the volume ratio of the calcium sulfate nanorod particles, norbornene-modified collagen, and tetraazine-modified hyaluronic acid is 1–5:100:

100. The method for preparing the calcium sulfate nanorod particles includes: Sulfuric acid and the first solvent are mixed evenly to form a first mixed system; The calcium salt and the first solvent are mixed evenly to form a second mixed system; The first mixture was added dropwise to the second mixture at a rate of 0.4–1.0 mL / min, and the mixture was mixed evenly to form a third mixture. The mixture was reacted at 20–30 °C for 6–24 h, and the solid obtained from the reaction was freeze-dried to obtain calcium sulfate nanorod particles. The calcium salt is selected from any one or a combination of two or more of calcium nitrate, calcium carbonate, and calcium phosphate. The first solvent is selected from anhydrous ethanol and / or methanol. The volume ratio of the first solvent in the first mixed system to the first solvent in the second mixed system is 5 to 10:

1. The molar ratio of calcium ions in the calcium salt to sulfate ions in sulfuric acid is 1 to 2:

1.

2. The preparation method according to claim 1, characterized in that, The method for preparing norbornene-modified collagen further includes: after the reaction of the fifth mixing system is completed, dialyzing the obtained reaction mixture for 1 to 3 days, and then freeze-drying it to obtain norbornene-modified collagen.

3. The preparation method according to claim 1, characterized in that, The method for preparing tetrazine-modified hyaluronic acid further includes: after the reaction of the seventh mixed system is completed, dialyzing the obtained reaction mixture for 1 to 3 days, and then freeze-drying it to obtain tetrazine-modified hyaluronic acid.

4. The preparation method according to claim 1, characterized in that: The condensing agent is selected from any one or a combination of two of benzotriazole-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride.

5. The preparation method according to claim 1, characterized in that: The second or third solvent is selected from any one or a combination of two or more of 2-(N-morpholino)ethanesulfonic acid, dichloromethane, tetrahydrofuran, and dimethyl sulfoxide.

6. An injectable self-mineralizing composite hydrogel prepared by any one of claims 1-5, comprising a mineralizing / osteoconductive substance dispersed within the hydrogel.

7. The injectable self-mineralizing composite hydrogel according to claim 6, characterized in that: The content of the mineralizing / osteogenic substances in the injectable self-mineralizing composite hydrogel is less than 5 wt%.

8. The injectable self-mineralizing composite hydrogel according to claim 6, characterized in that: The injectable self-mineralizing composite hydrogel has a porous structure with pores having a diameter of 200–400 μm.

9. The use of the injectable self-mineralizing composite hydrogel according to claim 7 or 8 in the preparation of products with bone defect repair function.